Fear of Crime During Years of Street Violence Is Associated With Worsening Cardiovascular Health Status - Oscar H. Del Brutto; Robertino M. Mera; Victor J. Del Brutto; Denisse A. Rumbea; Emilio E. Arias; Mark J. Sedler (Journal of Primary Care & Community Health)
Background: Street violence has detrimental effects on cardiovascular health (CVH). However, the significance of these consequences have not been systematically evaluated. In this study, we aimed to assess the impact of fear of crime on CVH status among community-dwellers aged ≥40 years living in a rural village stricken by violence. Methods: Participants were selected from individuals enrolled in the Atahualpa Project Cohort, a population-based longitudinal study that aims to reduce the burden of cardiovascular risk factors and diseases in rural Ecuador. Fear of crime was evaluated using a structured scale. The Life’s Simple 7 construct of the American Heart Association was employed to assess CVH before the escalation of violence and crime in the village (2019) and at the end of the study (2024). Multivariate logistic regression models were fitted to examine the association between the exposure and outcomes. Results: A total of 648 individuals (mean age = 57.4 ± 11.7 years; 56% women) were included. At the end of the follow-up, significant association between fear of crime levels and worsening CVH status was noted. Participants allocated to the second and third tertiles of fear of crime were 3.27 (95% CI = 2.07-5.19) and 5.46 (95% CI = 3.14-9.48) times more likely to have worsening CVH status at follow-up compared to baseline determinations, respectively. Conclusion: This study shows an aggravating impact of fear of crime on the CVH status and identifies interventional targets that may help to reduce the risk of CVH status worsening in community-dwellers living in rural settings afflicted by violence.